2019
DOI: 10.1093/mnras/stz967
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Rastall parameters in static space–times with galaxy-scale strong gravitational lensing

Abstract: Recently, Rastall gravity is undergoing a significant surge in popularity. We obtain a power-law total mass-density profile for the inner region (within several effective radius) of early-type galaxies (ETGs) from the space-time structures which are described by the static spherically-symmetric solutions of Rastall gravity under the assumption of perfect fluid matter. We find that in the inner region of ETGs, the Rastall dimensionless parameter β = κλ determines the mass distribution. We then use 118 galaxy-ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 43 publications
6
23
0
Order By: Relevance
“…Positive values of λ increased the stability regions whereas negative values decreased them in comparison to General Relativity. It should be remarked that the values of the Rastall parameter considered here are consistent with the ones obtained from a statistical analysis of 118 galaxy-galaxy strong gravitational lensing systems within the context of RG [41]. Remarkably, we found that for the radiation case (extremal and non-extremal cases) is possible to have thin-shell wormholes supported by nonrelativistic matter provided the relation β 0 = v 2 sound ≪ 1 holds.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Positive values of λ increased the stability regions whereas negative values decreased them in comparison to General Relativity. It should be remarked that the values of the Rastall parameter considered here are consistent with the ones obtained from a statistical analysis of 118 galaxy-galaxy strong gravitational lensing systems within the context of RG [41]. Remarkably, we found that for the radiation case (extremal and non-extremal cases) is possible to have thin-shell wormholes supported by nonrelativistic matter provided the relation β 0 = v 2 sound ≪ 1 holds.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, the statistical analysis based on the galaxy-galaxy strong gravitational lensing indicated that the Rastall' s parameter β = κλ is non-zero but is order of unity [41], supporting the idea that at the galactic scale it is possible to distinguish both theories. Moreover, the Bayesian analysis performed to constrain the rotation curves of 16 low surface brightness spiral galaxies showed that the Rastall's parameter β is of order 10 −1 [42], which is consistent with the strong lensing estimation [41]. At the cosmological scale, the supernovae type Ia data associated with the Constitution sample put stronger bounds on the Rastall's parameter, yielding to β ≃ O(10 −4 ) [43,44].…”
Section: A Black Hole Surrounded By An Anisotropic Fluid In Rgmentioning
confidence: 76%
See 2 more Smart Citations
“…Using realistic equations of state for the neutron star interior, an astrophysical constraint is placed on the Rastall gravity suggests that it is well consistent with GR as | | 10 −2 [99]. In contrast, the study [100] on much larger scales, using 118 galaxy-galaxy strong gravitational lensing systems, reports the constraint = −0.163 ± 0.001 (68% CL) excluding GR. Here, we study the robust and accurate observational constraints on the Rastall gravity extension of the standard CDM model.…”
Section: Introductionmentioning
confidence: 97%